Transvaginal Repair of Complex Rectovaginal Fistulas Using the Porcine Urinary Bladder Matrix as an Augmenting Graft. Issue 3 (May 2017) - Devakumar, Hemikaa; Chandrasekaran, Neeraja; Alas, Alexandriah; Martin, Laura; Davila, G. Willy; Hurtado, Eric
Abstract : Background: After the US Food and Drug Administration issued a safety warning concerning vaginal mesh implants in 2008, their use in correction of pelvic floor defects have decreased in the United States (http://www.fda.gov/NewsEvents/Newsroom/PressAnnouncements/ucm479732.htm ). However, we are still treating patients who have had complications associated with their use, rectovaginal fistulas (RVFs) being one of them. Rectovaginal fistulas are considered complex if greater than 2.5 cm, recurrent, associated with inflammatory bowel disease, or if they are proximal in location. Various surgical techniques have been described for treating RVFs. Interposition grafts such as Martius, gracilis, omental J flaps, and rectus abdominis flaps have been used extensively in correcting RVFs ( Am J Gastroenterol 2014;109(8):1141–1157). However, these techniques may increase morbidity or have poor cosmesis. Pelvic surgeons have chronicled the use of biologic grafts for fistula repair. Of the various biologic grafts in use, there have been no reports describing the use of porcine urinary bladder matrix (UBM) for fistula repair. We report on 2 cases of large, complex RVFs secondary to mesh erosion, which were effectively treated with transvaginal repair using the UBM. Cases: An 80-year-old woman was referred by the colorectal service to our urogynecology service with complaints of rectal bleeding and vaginal spotting secondary to mesh erosion. Surgical history included hysterectomy with mesh augmented posterior repair with synthetic midurethral sling placement in 2002. Examination revealed a 3-cm mesh exposure located in the middle third of the posterior vaginal wall. On rectovaginal examination, a 3-cm full-thickness RVF with through-and-through mesh erosion was noted between the rectum and vagina. A 65-year-old woman presented to our service with complaints of passage of fecal material through the vagina. Surgical history was significant for hysterectomy in 1988 and prolapse repair with anterior and posterior vaginal mesh in 2009. Subsequently in 2011, she had part of the mesh removed because of exposure. Vaginal examination revealed mesh exposure at the right sulcus of the anterior wall consistent with evidence of prior sling and another mesh exposure on the posterior vaginal wall. Rectovaginal examination revealed palpable mesh in the rectovaginal septum with a 3-cm large and complex fistula. Both of our patients underwent transvaginal excision of mesh, RVF repair, and posterior repair with augmentation with UBM. At 6- and 10-month follow-up, they reported complete resolution of their symptoms with no fistula noted on physical examination. Conclusions: Typically, traditional repair with use of muscular advancement flaps is performed for complex RVF closures. Recently, however, various biologic agents have been successfully used to augment RVF repair. In our cases, the use of UBM led to successful follow-up at 6 to 8 months. Despite existing literature, there remains a void in the depth of knowledge regarding the UBM grafts. Larger studies utilizing it for repair of RVFs are warranted to further understand the success and effectiveness of the UBM grafts for RVF repair. Abstract : Safe use of the porcine urinary bladder matrix for the repair of complex rectovaginal fistulas attributed to vaginal mesh implants.